Urgent surgery in colon cancer has no impact on survival - Antony, Pia-Anita; Harnoß, Julian-Camill; Schneider, Martin (Journal of surgical oncology, 2019)
Background and objectives Despite advances in early detection of colon cancer, a minority of patients still require urgent surgery. Whether such urgent conditions result in poor outcome remains a topic of debate. Methods Using a prospectively maintained database, patients suffering exclusively from colon cancer and receiving either elective or emergent resection between 2001 and 2014 were analyzed with respect to overall, disease-specific, and relative survival using Cox regression and propensity score analyses. Results From a total of 877 patients analyzed, 2.7% (24) presented with complications requiring urgent surgery. Propensity-scoring identified strongly biased patient characteristics (0.097 ± 0.069 vs 0.028 ± 0.043; P < 0.001). An unadjusted Cox proportional hazards regression analysis revealed urgent surgery as a statistically significant prognostic factor with an approximately 207% increased risk of mortality (hazard ratio [HR] = 3.07; 95% confidence interval [CI]: 1.62-5.81; P = 0.003). After adjusting the data according to the propensity score analysis, urgent surgery was not associated with a decreased overall (HR = 1.67; 95%CI; 0.84-3.36; P = 0.174), disease-specific (HR = 1.62; 95% CI; 0.81-3.24; P = 0.201) or relative survival (HR = 1.86; 95% CI: 0.92-3.79; P = 0.086). Conclusions After risk-adjustment, using multivariable Cox regression and propensity score analyses, no significant disadvantage could be noted with regard to overall, disease-specific, or relative survival in patients with exclusively colon cancer who received emergent oncological resection.
Gesehen am 23.09.2019